Application oriented cross-layer multi-channel MAC protocol for VANET - Cai-xia SONG; Guo-zhen TAN; Nan DING; Jun-ling BU; Fu-xin ZHANG; Ming-jian LIU (Tongxin xuebao)
An application oriented cross-layer multi-channel(AOCM)MAC protocol was proposed for VANET.The AOCM protocol could derive the optimal control channel(CCH)interval to ensure the timely and reliable transmission of safety messages on the CCH,based on real-time statistics and prediction for different types of sages coming from upper application layer.In the service channels(SCH),the proposed protocol relies on a reservation mechanism for con-tention-free transmission,so as to improve the throughput of SCH.The proposed protocol was suitable for both saturation and unsaturation conditions,and has low computational complexity and high scalability.Extensive simulation results demonstrate the superiority of the AOCM protocol compared with other existing protocols.